Application of Fuzzy TOPSIS Method in Scholarship Interview - Abduh Riski; Ahmad Kamsyakawuni (UPT Penerbitan Universitas Jember, 2016)
Decision-making problem is the process of determines the best options of all feasible alternative. In some problems, decision-making process involves the attributes of linguistic as in scholarship interview, which is one of the multi-objective decision-making (MODM) problem. The aim of this paper is to apply Fuzzy TOPSIS method in scholarship interview. Scholarship Interview that defined in this paper was implemented to candidates by questions for each candidate and assessed by interviewers. Technique for the Order of Preference by Similarity to Ideal Solution (TOPSIS) method is a multi-attribute decision-making (MADM) method. The basic principle of the TOPSIS method is to choose the alternative that has similarity with the ideal solution. So that the TOPSIS method can be applied in a scholarship interview, in the first step is used fuzzy method to reduce the -dimensional objective space to be one-dimensional objective space. Then applied the TOPSIS steps by fuzzy approaching to find the best alternative. In this paper will be used a scholarship interview case to illustrate more obviously steps. With this approach, the determination of the scholarship recipients can be more powerful and assured.